Gelatin promotes cell aggregation and pro-inflammatory cytokine production in PMA-stimulated U937 cells by augmenting endocytosis-autophagy pathway. (February 2018) - Zhao, Ye-Li; Lu, Zhuo-Yu; Zhang, Xuan; Liu, Wei-Wei; Yao, Guo-Dong; Liu, Xiao-Ling; Liu, Wei; Wu, Qing-Jie; Hayashi, Toshihiko; Yamato, Masayuki; Fujisaki, Hitomi; Hattori, Shunji; et al.
Abstract: Gelatin, denatured collagen, temporarily exists in tissues and may well be pathophysiologically involved in tissue remodeling, inflammation or tissue damage. The present study is aimed to investigate possible biological roles of gelatin by examining its effects on monocyte-like histiocytic lymphoma cell line U937. Once stimulated by phorbol 12-myristate 13-acetate (PMA), U937 cells differentiate into macrophage-like cells, changing from non-adherent to adherent cells with extended pseudopodia. Here we pre-treated the cell dishes with gelatin solution for cell culture. Interestingly, we found that PMA-stimulated U937 cells formed multicellular aggregates on gelatin-coated dishes, accompanying NF-κB-mediated production of pro-inflammatory cytokines, whereas cell aggregation was not detected on non-coated dishes. Moreover, differentiated U937 cells on gelatin-coated dishes showed increased autophagy level and endocytosis. Surprisingly, formation of multicellular aggregates and pro-inflammatory cytokine production were both attenuated by either down-regulation of autophagy with inhibitors, such as 3-methyladenine (3MA) or chloroquine (CQ), or repression of endocytosis with siRNA targeting Endo180. Moreover, autophagy was inhibited by si-Endo180, and endocytosis was suppressed by 3MA, suggesting a positive feedback loop between autophagy and endocytosis. The results revealed that gelatin-coating induced differentiated U937 cells to form cell aggregates and promote NF-κB-mediated pro-inflammatory cytokine production at least partially through an endocytosis-autophagy pathway.